Hubungan Implementasi Rekam Medis Elektronik (RME) dengan Kualitas Pelayanan Kesehatan di Wilayah Kerja UPT Puskesmas Rappang Kabupaten Sidenreng Rappang Provinsi Sulawesi Selatan - Reski Idris; Sunandar Said; Pratiwi Ramlan (Malahayati Nursing Journal, 2025)
ABSTRACT This study aims to analyze the relationship between the implementation of Electronic Medical Records (EMR) and the quality of healthcare services in the UPT Puskesmas Rappang work area, Sidenreng Rappang Regency, South Sulawesi Province. The objective of this research is to determine the relationship between the speed of service of Electronic Medical Records (EMR) and the frequency of network errors/disruptions on the quality of healthcare services. This study employs a quantitative approach with a cross-sectional method. The sampling technique was conducted using simple random sampling with the Slovin formula, resulting in a sample of 91 patients in the Puskesmas Rappang work area. Data was collected through questionnaires distributed to patients, as well as secondary data from reports on the use of Electronic Medical Records (EMR) in several auxiliary community health centers (Pustu) and health posts (Poskesdes) in the region. Data analysis was conducted using the Chi-Square test to observe the relationship between the implementation of Electronic Medical Records (EMR) and the quality of healthcare services. The results showed that the p-value was greater than the set significance threshold (p 0.05), indicating that there is no significant relationship between the speed of service and error frequency of Electronic Medical Records (EMR) with the quality of service in the UPT Puskesmas Rappang work area. Keywords: Electronic Medical Records, Quality of Health Services, Public Health Centers, Patient Satisfaction.  ABSTRAK Penelitian ini bertujuan untuk menganalisis Hubungan Implementasi Rekam Medis Elektronik (RME) dengan Kualitas Pelayanan Kesehatan di Wilayah Kerja UPT Puskesmas Rappang, Kabupaten Sidenreng Rappang, Provinsi Sulawesi Selatan. Tujuan penelitian ini adalah untuk mengetahui hubungan antara kecepatan pelayanan Rekam Medis Elektronik (RME) dan frekuensi error/gangguan jaringan terhadap kualitas pelayanan kesehatan.Penelitian ini menggunakan pendekatan kuantitatif dengan metode cross-sectional. Teknik pengambilan sampel dilakukan secara simple random sampling dengan menggunakan rumus Slovin, menghasilkan sampel sebanyak 91 orang pasien di wilayah kerja Puskesmas Rappang. Data dikumpulkan melalui kuesioner yang dibagikan kepada pasien, serta data sekunder dari laporan penggunaan Rekam Medis Elektronik (RME) di beberapa Puskesmas Pembantu (Pustu) dan Poskesdes di wilayah tersebut. Analisis data dilakukan menggunakan uji Chi-Square untuk melihat hubungan antara implementasi Rekam Medis Elektronik (RME)  dengan kualitas pelayanan kesehatan. Hasil penelitian menunjukkan bahwa nilai p-value lebih besar dari batas signifikansi yang ditetapkan (p 0,05), sehingga tidak terdapat hubungan yang signifikan antara kecepatan pelayanan dan frekuensi eror dari Rekam Medis Elektronik (RME) dengan kualitas pelayanan di wilayah kerja UPT Puskesmas Rappang. Kata Kunci: Rekam Medis Elektronik, Kualitas Pelayanan Kesehatan, Puskesmas,  Kepuasan Pasien.